International organizations - Archer, Clive (London ; New York : Routledge, 2001)
The third edition of Clive Archer's widely used textbook continues to provide students with an introduction to international organisations, exploring their increasing significance in the modern international political systems.
1. Definitions and History 2. Classification of International Organisations 3. Writings on International Organisations 4. Role and Function of International Organisations 5. International Organisations - The Future
Includes bibliographical references (pages [182]-197) and index.
Keywords: International agencies